2018
DOI: 10.3390/jcm7090250
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Frailty Predicts Incident Dementia among Community-Dwelling Older People

Abstract: Cognitive frailty, defined as the presence of both frailty and cognitive impairment, is a risk factor for adverse events in older adults. However, prevalence rates of cognitive frailty are low (1.1–2.5%), so primary screening is unsuitable in community settings. The aim of the study was to examine whether a new definition of cognitive frailty, which was developed for primary screening, is useful to predict incident dementia in community-dwelling older adults. A total of 4570 older adults participated in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 61 publications
2
51
1
1
Order By: Relevance
“…Most previous studies on frailty have only focused on the physical dimension [16,17,38], though there is some evidence showing a relationship between mental status and social relations and incident dementia. In a Japanese dementia study, Shimada interviewed 4570 community-dwelling elderly persons and found that inclusion of a cognitive dimension in the frailty assessment improved the predictive accuracy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on frailty have only focused on the physical dimension [16,17,38], though there is some evidence showing a relationship between mental status and social relations and incident dementia. In a Japanese dementia study, Shimada interviewed 4570 community-dwelling elderly persons and found that inclusion of a cognitive dimension in the frailty assessment improved the predictive accuracy [39].…”
Section: Discussionmentioning
confidence: 99%
“…CF was designated with the goal of identifying individuals with reduced cognitive reserve that is a potentially reversible consequence of frailty rather than the result of neurodegenerative disorders [3]. CF is reported to increase the incidence of dementia [4], and it is associated with adverse health outcomes, such as functional decline, disability, poor quality of life [5], and increase in mortality [6]. This calls for the urgent formulation of a preventive action plan against the development of CF among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…CF has been consistently shown to increase the risk of the progression toward dementia among older adults [4,7]. It was highlighted in the Singapore Longitudinal Ageing Studies (SLAS) that the risk of neurocognitive disorders increased three times among older adults with the co-existence of physical frailty and cognitive impairment, as compared to those with a single syndrome [8].…”
Section: Introductionmentioning
confidence: 99%
“…The power analysis we used is based on the proportion of incident dementia. We based our sample size calculation on the cumulative incidence of dementia in our previous study [9]. Enrollment of 5390 participants provided 80% power to detect a 33% between‐group difference in the cumulative incidence of dementia, with a two‐sided α level of 0.05.…”
Section: Methodsmentioning
confidence: 99%